PENGARUH BEBERAPA JENIS PESTISIDA NABATI TERHADAP HAMA ULAT GRAYAK (Spodoptera litura F.) PADA TANAMAN SAWI (Brassica Juncea L ) DI LAPANGAN - Maksimilianus Bate (AGRICA, 2019)
This study aims to determine the effect of extracts of tobacco plants, cloves, lemongrass, neem seeds, and chillis on the development of gray pests caterpillars Spodoptera litura F. and determine sure plant extracts against armyworms. The design used was a randomized group design (RCBD) with the treatment of 5 types of vegetable pesticides, namely E1 (tobacco extract) E2 (clove extract) E3 (citronella extract) E4 (neem extract) E5 (red chili extract). The observational variables in this study were insects intensity, pest mortality, plant fresh weight, and original weight per hectare. The results showed that five types of vegetable pesticide extract affected the armyworm Spodoptera litura F. Tobacco leaf extract was an appropriate and effective plant against the mortality of armyworm by 32%. The lowest insect intensity in the treatment of tobacco extract by 25%, fresh weight of planting mustard was equal to 112, 85 gr, and the original weight of plants per hectare amounted to 28.21 tons.